The Impact of Firm Size on Profitability – A Study on the Top 10 Cement Companies of Pakistan - Talha Akram; Muhammad Usman Farooq; Hamza Akram; Abdul Ahad; Muhammad Numan (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2021)
The research is conducted on the “The impact of Firm Size on Profitability – A Study on the Top 10 Cement Companies of Pakistan”. The data was taken from the top 10 cement firms which are listed on the Pakistan stock exchange (PSX). The purpose of this study was to understand how firm size can have an impact on profitability in a developing country like Pakistan and to evaluate what variables play an important role in it. The secondary data was collected by different annual reports published by the companies. The research is based on panel data with multiple regression model run for return on assets (ROA) and return on equity (ROE) which are the dependent variables in this study. The independent being the firm size determined by total assets and total sales. The findings show and conclude that when firm size is determined by total sales value it shows a positive impact with ROA and ROE. Whereas, when determined by total assets value, it show a negative impact. Overall, the relationship is of a significantly weak impact with that of firm size on the profitability which shows a blend of positive and negative impact as well.